Anti-inflammatory effects of topical lactobacillus acidophilus and antibiotic in wound repair on the basis of microscopic parameters: a comparative study in rats - Khan, Hina; Jiskani, Asad R.; Kumari, Devi; Rafique, Muhammad; Kirmani, Fouzia; Azmi, Muhammad A. (International Journal of Research in Medical Sciences, 2019)
Background: Wound treatment still a task for medical professionals, according to the time advancement. We need to elaborate further new interventions to cope up this common factor of community. The objective of the study was to assess the anti-inflammatory topical role of Lactobacillus acidophilus with antibiotic in wound repair of rats based on of microscopic parameters. This comparative study was conducted in the Department of Anatomy Al-Tibri Medical Collage and Hospital Isra University Karachi Campus from December 2018 to April 2019. Methods: Total 18 male of wistar rats were randomly selected for this study. The study comprised of three topical groups Control, Antibiotic and Lactobacillus acidophilus groups respectively. Results: The samples were taken from the wound site for the preparation of microscopic slides, to count the numbers of neutrophils, lymphocytes and macrophages for the evaluation of anti-inflammatory process in both groups on day 3 and 7. Data obtained were analyzed by SPSS version 20 by applying One Way ANOVA and post hoc Tukey’s test. Conclusions: The results were shown potent anti-inflammatory effects of Lactobacillus acidophilus group in comparison with other conventional therapy. The study concludes that the topical application of Lactobacillus acidophilus had remarkable anti-inflammatory effects in wound management.